POPULATION DOCUMENTATION OF PELUNG CHICKEN IN FIVE SUB DISTRICTS IN GARUT REGENCY - wulan anisha mahdayanti; Indrawati Yudha Asmara; Dani Garnida (Jurnal Produksi Ternak Terapan, 2023)
Pelung chicken is a local Indonesian chicken originating from Cianjur.  The Pelung population data is still not known with certainty. This study aims to obtain the total and structure of  population, determine the effective population size (Ne), and the rate of inbreeding (∆F) in Pelung chickens in five districts in Garut Regency. This research was conducted from May to June 2022 in Cikajang, Pasirwangi, Bayongbong, Samarang, and Cigedug Districts. The study used, quantitative descriptive methods and data were obtained by direct interview techniques in which a total of respondents were interviewed.  The results of the study showed that the total population of Pelung chickens at the research location was 1,867 Pelung chickens with 452 birds in district of Cikajang, 316 of Pasirwangi, 555 of Bayongbong, 194 of Samarang, and 350 of Cigedug. The total number of effective population sizes at the study site was 465 individuals.  The inbreeding rate per generation in five sub-districts was 0.1%, with the highest inbreeding rates in Samarang 0.82%, followed by Cigedug 0.78%, Pasirwangi 0.54%, Cikajang 0.42%, and Bayongbong 0.39%.